Superior vena cava blood flow and Doppler indices of brain sparing in late onset fetal growth restriction - Maria Stefopoulou; Jonas Johnson; Peter Lindgren; Ganesh Acharya (Scientific Reports)
Abstract Cerebral hemodynamic adaptation in fetal growth restriction (FGR) is primarily assessed using middle cerebral artery (MCA) Doppler and cerebroplacental (CPR) or umbilicocerebral ratio (UCR). The superior vena cava (SVC) blood flow may provide additional hemodynamic insights. Our objective was to evaluate fetal SVC blood flow velocities, pulsatility index for vein (PIV), volume blood flow (QSVC), and volume blood flow (Q)-based indices of fetal brain sparing in small-for-gestational-age (SGA) and FGR fetuses in the third trimester of pregnancy and compare with appropriately grown (AGA) fetuses. This was a prospective cohort study of 40 non-anomalous, singleton fetuses during 32 + 0 to 36 + 6 gestational weeks. Fetuses with abdominal circumference or estimated fetal weight below the 10th percentile were classified into SGA and FGR groups based on Delphi criteria. Doppler velocimetry of the umbilical artery (UA), umbilical vein (UV), fetal MCA and SVC was performed. UV and SVC diameters were measured, and their volume blood flows, i.e. QUV and QSVC were calculated. Both pulsatility index (PI)-based and Q-based indices of fetal brain sparing were calculated and compared to previously reported reference ranges for AGA fetuses using z-scores. In our study population, z-scores of SVC velocities (except the end-diastolic A-wave velocity) and PIV were significantly lower than the gestational age-specific mean values for AGA fetuses (p-values 0.005 to 0.018). Similarly, z-scores of SVC diameter (p < 0.001), QSVC normalized to fetal weight (QSVCw) (p < 0.001), blood flow volume-based QCPR (p < 0.001) were higher and QUCR (p < 0.001) was lower. However, z-scores of PI-based CPR (p = 0.195), UCR (p = 0.195), and the end-diastolic (A wave) velocity (p = 0.177) were not significantly different compared to AGA fetuses. Subgroup analysis demonstrated that the FGR fetuses (n = 21) had increased SVC diameter (p < 0.001), QSVCw (p < 0.001), QCPR (p < 0.001), UCR (p < 0.001), and decreased CPR (p < 0.001), QUCR (p < 0.001) and SVC PIV (p = 0.030), but no significant change in velocities was observed compared to AGA fetuses (n = 98) of similar gestational age. The SGA fetuses (n = 19) had decreased SVC S velocity (p = 0.013), D velocity (p = 0.005), TAMxV (p = 0.030), PIV (p = 0.005), QUCR (p = 0.014), and increased SVC diameter (p = 0.026), QSVCw (p = 0.034) and QCPR (p = 0.014) in comparison to AGA fetuses. When compared to SGA fetuses, the FGR fetuses had significantly lower QUVw (60.5 ± 19.7 vs. 80.1 ± 20.2 ml/min/kg, p = 0.004), QUCR (0.79 ± 0.45 vs. 1.34 ± 0.52 p < 0.001) and birthweight (2181 ± 577 vs. 2848 ± 330 g, p < 0.001) but higher QSVCw (91.82 ± 39.56 vs. 65.53 ± 17.79 ml/min/kg, p = 0.039) and QCPR (1.63 ± 0.74 vs. 0.90 ± 0.45, p < 0.001). In conclusion, third-trimester fetuses < 10th percentile had significantly increased SVC diameter, resulting in increased QSVCw in SGA and FGR despite reduced or unchanged TAMxV. Significantly altered QCPR and QUCR confirmed circulatory redistribution with increased brain and upper body venous return both in FGR and SGA fetuses. However, as the magnitude of increase in QSVCw and QCPR was significantly larger in FGR compared to SGA fetuses, it could be potentially used as a quantifiable marker to differentiate FGR from SGA. The role of SVC Doppler in refining the diagnosis of late FGR should be further investigated.